(untitled) (Faridpur Medical College Journal, 2016)
Back pain resulting from degenerative disease of the spine is one of the most common causes of disability in adults of working age. The structures which may be responsible for the origin of the degenerative spine are bone (spondylolisthesis, spondylolysis), ligaments (hypertrophy of the spinal ligaments, particularly the ligamentum flavum), facet joints (facet hypertrophy, synovial cyst) and intervertebral disc (bulging and herniation)1. This was a cross sectional study of 105 patients with low back pain. All Plain X-ray and MRI findings were collected for each patient in a pre-designed structured data collection sheet. In plain X-ray 74 subjects had posterior disc height <6mm; out of them nerve root compression found in 56, spinal stenosis found in 54. Those who had posterior osteophytes, (86.8%) found to have disc herniation. Among facetal hyperthrophy (72 subjects), 62 (86.1%) had disc herniation. In this study significant correlation found between plain radiographic findings of degenerative changes of lumbosacral spine with MRI. Faridpur Med. Coll. J. Jul 2015;10(2): 68-70